Transforming growth factor-β-induced gene product-h3 inhibits odontoblastic differentiation of dental pulp cells. (June 2017) - Serita, Suguru; Tomokiyo, Atsushi; Hasegawa, Daigaku; Hamano, Sayuri; Sugii, Hideki; Yoshida, Shinichiro; Mizumachi, Hiroyuki; Mitarai, Hiromi; Monnouchi, Satoshi; Wada, Naohisa; Maeda, Hidefumi
Highlights: βig-h3 expression in dental pulp tissue was attenuated after pulp capping treatment. IL-1β and TNF-α inhibited βig-h3 gene expression. These cytokines induced odontoblastic differentiation of HDPCs. Exogenous βig-h3 inhibited odontoblastic differentiation of HDPCs. βig-h3 gene silencing promoted expression of odontoblast-related genes in HDPCs. Abstract: Objective: The aim of this study was to investigate transforming growth factor-β-induced gene product-h3 (βig-h3) expression in dental pulp tissue and its effects on odontoblastic differentiation of dental pulp cells (DPCs). Design: A rat direct pulp capping model was prepared using perforated rat upper first molars capped with mineral trioxide aggregate cement. Human DPCs (HDPCs) were isolated from extracted teeth. βig-h3 expression in rat dental pulp tissue and HDPCs was assessed by immunostaining. Mineralization of HDPCs was assessed by Alizarin red-S staining. Odontoblast-related gene expression in HDPCs was analyzed by quantitative RT-PCR. Results: Expression of βig-h3 was detected in rat dental pulp tissue, and attenuated by direct pulp capping, while expression of interleukin-1β and tumor necrosis factor-α was increased in exposed pulp tissue. βig-h3 expression was also detected in HDPCs, with reduced expression during odontoblastic differentiation. The above cytokines reduced βig-h3 expression in HDPCs, and promoted their mineralization. Recombinant βig-h3 inhibited the expression of odontoblast-related genes and mineralization of HDPCs, while knockdown of βig-h3 gene expression promoted the expression of odontoblast-related genes in HDPCs. Conclusions: The present findings suggest that βig-h3 in DPCs may be involved in reparative dentin formation and that its expression is likely to negatively regulate this process.